(untitled) (Texas Journal of Philology, Culture and History, 2024)
Chronic obstructive pulmonary disease (COPD) is a pressing problem in the modern world. Every year, COPD increasingly leads to temporary disability and death. This is why it is so important to predict the progression of COPD in time. Progression of the disease can lead to severe shortness of breath, frequent exacerbations of COPD, respiratory failure and death. This literature review examines radiological and functional markers, clinical manifestations, sputum and blood markers, and the lung microbiome. All of this may be useful for predicting the risk of COPD progression